Cloud-based radio frequency identification authentication protocol with location privacy protection - Qingkuan Dong; Mengmeng Chen; Lulu Li; Kai Fan (International Journal of Distributed Sensor Networks)
With the development of the Internet of things and cloud storage, a large number of objects access to the Internet through radio frequency identification technology, cloud-based radio frequency identification system attracts more attention because it can reduce the costs of system maintenance by renting the cloud storage service on demand. Especially, it is very suitable for the small- and medium-sized enterprises. However, the security and privacy issues of the cloud-based radio frequency identification system are more serious than traditional radio frequency identification systems. The link between the reader and the cloud is no longer secure, and the cloud service provider is not trusted. Both the location privacy of the reader and the data privacy of the radio frequency identification system are not able to be exposed to the cloud service provider. In this article, a cloud-based radio frequency identification authentication protocol is proposed. It considers not only the mutual authentication between the reader and the tag, but also the security of data transmission between the reader and the cloud database. In particular, in order to solve the reader’s location privacy problem, the proposed scheme introduces MIPv6 network framework without adding additional infrastructure. The experimental verification with AVISPA tool shows that the protocol satisfies the mutual authentication property. Compared with other cloud-based schemes, the proposed protocol has obvious advantages in deployment cost, scalability, real-time authentication, and the tag’s computational complexity.